Realizacja Krajowego Programu Oczyszczania Ścieków na przykładzie wybranych gmin = Implementation of the national programme of wastewater treatment - Sadecka, Zofia; Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
National Programme for municipal wastewater treatment determines the project for the construction, expansion and/or modernization of sewage collecting and waste water treatment plant, as well as deadlines for their implementation. Comply with these obligations is shown in the example of some municipalities.
Keywords: Krajowy Program Oczyszczania Ścieków Komunalnych (KPOŚK); gmina; National Programme for municipal wastewater treatment (KPOŚK); municipality